General Ordinances of the City of Aspen, § 182, in Aspen Daily Times, Jul. 27, 1886, at 3-6 - (:unkn) unknown (My University, 1886)
If any person shall, within the corporate limits of the city of Aspen, have, concealed upon his person any pistol, bowie-knife, dagger, slung-shot, billy, dirk-knife, brass or metal knuckles, or other deadly weapon, he or she shall, on conviction, be fined in any sum not less than five nor more than one hundred dollars, in the discretion of the court, or be imprisoned in the city jail at hard labor not less than five nor more than ten days, in the discretion of the court, or both such fine and imprisonment in the discretion of the court, for every such offense.
Keywords: CARRY - CONCEALED